Burger's Medicinal Chemistry and Drug Discovery 2003
DOI: 10.1002/0471266949.bmc035
|View full text |Cite
|
Sign up to set email alerts
|

Retrometabolism‐Based Drug Design and Targeting

Abstract: Retrometabolic approaches represent systematic drug design methodologies that thoroughly integrate structure—activity and structure—metabolism relationships and are aimed to design safe compounds with an improved therapeutic index. They incorporate two major concepts aimed to design soft drugs and chemical delivery systems, respectively. Soft drugs are new, active therapeutic agents that undergo predictable metabolism to inactive metabolites after exerting their desired therapeutic effect. Chemical delivery sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 346 publications
0
8
0
Order By: Relevance
“…Soft anticholinergic agents designed (Figure ) using the soft drug approach of the general retrometabolism-based drug design and targeting concept can provide viable solutions for the problems faced during the development of local anticholinergics. Soft drugs are biologically active molecules, often isosteric/isoelectronic analogues of a lead compound, specifically designed to allow predictable metabolism into inactive metabolites after exerting the desired therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft anticholinergic agents designed (Figure ) using the soft drug approach of the general retrometabolism-based drug design and targeting concept can provide viable solutions for the problems faced during the development of local anticholinergics. Soft drugs are biologically active molecules, often isosteric/isoelectronic analogues of a lead compound, specifically designed to allow predictable metabolism into inactive metabolites after exerting the desired therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, soft drugs are expected to produce pharmacological activity locally but be rapidly deactivated by metabolic (preferably hydrolytic) processes as they distribute away from their site of action to prevent any kind of undesired pharmacological activity or toxicity. Because a locally active soft anticholinergic, which has high local but practically no systemic activity, can provide a viable solution to many of the problems hindering the development of anticholinergic drugs, different series of soft anticholinergics based on methylatropine ( 1 ), N -methylscopolamine ( 2 ), glycopyrrolate ( 4 ), propantheline ( 5 ), or other lead structures were designed and tested during the last two-and-a-half decades (see refs and for detailed reviews).
1 The general design concept of soft anticholinergics agents.
…”
Section: Introductionmentioning
confidence: 99%
“…Slow and easily saturable oxidative pathways are avoided in favour of hydrolytic deactivation pathways. The main advantages of this approach in drug design are as follows: first, improvement of the therapeutic index by eliminating the formation of biologically active metabolites and toxic intermediates; second, elimination of many metabolic drug interactions by avoiding saturable enzymatic processes; and third, simplification of the drug pharmacokinetics (Bodor & Buchwald 2003). This leads to the formation of drugs with an enhanced margin of safety (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, in work related to the brain-targeted delivery of neuropeptides, we have shown that in various arginine (Arg, R)-, histidine (His, H)-or lysine (Lys, K)-containing peptides, the original basic amino acid could be replaced by novel redox amino acids (Nys ↔ Nys + ), which contain a 1,4dihydrotrigonelline ↔ quaternary trigonelline side-chain, without activity-loss due to the sufficiently close steric and electronic analogy between the quaternary form of the redox (Nys + ) and the original side-chains (in their protonated form, Arg + , Lys + ) ( Figure 1) (Chen et al 1998;Bodor & Buchwald 2003b). This analogy is further illustrated in Figure 2 by comparing kyotorphine (Tyr-Arg, YR), an endogenous neuropeptide that exhibits analgesic action through the release of endogenous enkephalin and has analgesic activity about four times larger than Met-enkephalin (Takagi et al 1979), and its redox analogue in its permanently charged form, Tyr-Nys + .…”
mentioning
confidence: 99%
“…This analogy is further illustrated in Figure 2 by comparing kyotorphine (Tyr-Arg, YR), an endogenous neuropeptide that exhibits analgesic action through the release of endogenous enkephalin and has analgesic activity about four times larger than Met-enkephalin (Takagi et al 1979), and its redox analogue in its permanently charged form, Tyr-Nys + . Incorporation of the Nys moiety into the structure of neuropeptides resulted in brain-targeted redox analogue (BTRA) peptides that made possible the non-invasive brain delivery of these important biomolecules in pharmacologically significant amounts (Chen et al 1998;Bodor & Buchwald 2003b), and the peptide with the Nys + amino acid, metabolically formed from the originally administered Nys form, produced CNS activity due to the close analogy of its quaternary nicotinamide-containing side-chain with kyotorphine's Arg sidechain, which is always ionized under physiological conditions. Therefore, it seemed reasonable to investigate whether the replacement of the guanidinium headgroups of arginines by such permanently charged Nys + redox amino acids still maintains the cell-penetrating activity of the molecular transporter peptides.…”
mentioning
confidence: 99%